2018
DOI: 10.1096/fj.201701408r
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by adoptive regulatory T‐cell transfer improves Coxsackievirus B3‐induced myocarditis

Abstract: Regulatory T (T) cells offer new therapeutic options for controlling undesired systemic and local immune responses. The aim of the current study was to determine the impact of therapeutic T administration on systemic and cardiac inflammation and remodeling in coxsackievirus B3 (CVB3) -induced myocarditis. Therefore, syngeneic T cells were applied intravenously in CVB3-infected mice 3 d after infection. Compared with CVB3 + PBS mice, CVB3 + T mice exhibited lower left ventricular (LV) chemokine expression, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 47 publications
2
41
0
1
Order By: Relevance
“…Although we found an overall reduction of CD4 + T cells in the heart in siCSF-1 treated mice, we cannot conclude on the influence of silencing the CSF-1 axis on CD4 + T cell differentiation e.g., into regulatory T cells or Th1 and Th17 cells. From our data we cannot conclude on possible additional effects e.g., of regulatory CD4 + T cells that are known to mitigate the inflammatory tissue damage in the heart ( 43 , 44 ). CSF-1 facilitates myeloid cell differentiation, monocyte survival, and macrophage proliferation.…”
Section: Discussionmentioning
confidence: 69%
“…Although we found an overall reduction of CD4 + T cells in the heart in siCSF-1 treated mice, we cannot conclude on the influence of silencing the CSF-1 axis on CD4 + T cell differentiation e.g., into regulatory T cells or Th1 and Th17 cells. From our data we cannot conclude on possible additional effects e.g., of regulatory CD4 + T cells that are known to mitigate the inflammatory tissue damage in the heart ( 43 , 44 ). CSF-1 facilitates myeloid cell differentiation, monocyte survival, and macrophage proliferation.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, Sacerdote et al only investigated splenocyte proliferation, NK activity and IL-2 production to determine the immunosuppressive potential of the used opioids [ 37 , 47 , 48 , 49 ]. Especially in models of inflammatory disease, like CVB3-induced myocarditis, it is well established that the extent of the immune response is not mediated by only one cell population or cytokine but rather by an orchestra of innate and adaptive immunity components [ 10 , 11 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, previous own studies investigated the impact of various cell populations in the context of CVB3-induced heart failure [ 11 , 65 ], including monocytes/macrophages, NK cells, and DCs [ 50 , 66 , 67 ]. With respect to opioid administration, Filipczak-Bryniarska and colleagues intensively reported modulation of monocytes/macrophages and NK cells, and corresponding release of pro-inflammatory cytokines by LPS-stimulated macrophages [ 33 , 64 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 + T lymphocytes are globally expanded and activated in chronic ischemic HF, with Th2 (vs. Th1) and Th17 (vs. Treg) predominance in failing hearts . In contrast, a wealth of evidence from experimental and clinical studies has indicated that CD4CD25FOXP3+ Tregs might have an important role in protecting against cardiovascular disease, including MI, myocarditis, dilated cardiomyopathy, and HF . In HF, Tregs are qualitatively and quantitatively impaired independently of the etiology and are consequently ineffective in regaining immune homeostasis.…”
Section: Antiinflammatory and Immunomodulatory Strategiesmentioning
confidence: 99%